Progesterone - effective for tocolysis and maintenance treatment after arrested preterm labour? - Rath, Werner; Kuon, Ruben-Jeremias (Geburtshilfe und Frauenheilkunde, 2019)
Numerous experimental studies indicate that natural progesterone, through various mechanisms, exerts an inhibitory effect on uterine contractility and sensitises the myometrium for tocolytics. It was therefore appropriate to investigate the possible benefits of oral/vaginal progesterone and the synthetic progesterone derivative 17-α-hydroxyprogesterone caproate, applied intramuscularly, in clinical studies on primary tocolysis, additively to established tocolytics (“adjunctive tocolysis”) and as maintenance treatment after successful tocolysis in cases of threatened preterm birth. Three studies with a small number of cases do not yield any sufficient evidence for recommending progesterone/17-α-hydroxyprogesterone caproate as primary tocolysis in women with preterm labour. There is also no evidence that progesterone or 17-α-hydroxyprogesterone caproate combined with commonly used tocolytics leads to a prolongation of pregnancy and a significant decrease in the rate of preterm birth. The data on the use of progesterone as maintenance treatment is controversial. While randomised, controlled studies with low quality showed promising results, studies with high quality did not reveal any significant differences with regard to the rate of preterm birth < 37 weeks of gestation, the latency period until delivery and in the neonatal outcome between progesterone/17-α-hydroxyprogesterone caproate and placebo or no treatment. Significant differences in the methodology, the inclusion and outcome criteria, the mode of application and the dosages of the substances as well as the inadequate statistical power as a result of low numbers of cases make interpretation and comparability of the studies difficult. Therefore, well-designed randomised, placebo-controlled, double-blind studies with uniform primary outcome criteria are needed in order to clarify whether progesterone and via which route of administration and at which dosage is of clinical benefit for patients with manifest preterm contractions and as maintenance treatment after arrested preterm labour.
Gesehen am 23.04.2020